KAJIAN EKSPERIMENTAL ROADCELL-50 SEBAGAI BAHAN TAMBAH (ADDITIVE) PADA CAMPURAN SPLIT MASTIC ASPAL (SMA) YANG MENGGUNAKAN MATERIAL LOKAL BATU TANGKILING - Davies Rahusan Saloh (Lambung Mangkurat University Press, 2013)
One of the developments in flexible pavement system is the Split Mastic Asphalt (SMA) mixture, which is specifically designed to increase durability, roughness, flexibility, flow resistance and oxidation resistance. This type of mixture is mainly used in roads with heavy traffics, or uphill roads. Based on the fact above and unmeasured traffic load, a research was conducted by adding Roadcell-50 to the SMA mixture by using local material from Batu Tangkiling. Later on, it is hoped that the result can optimize local material usage, which in turn will affect local income and improve the quality of asphalt mixture. The objective of this research is to identify the performance of SMA mixture without Roadcel-50 as an asphalt mixture additive; to identify Marshall characteristics by adding Roadcell-50 additive at the level of 0 percent; 0.2 percent; 0.3 percent, 0.4 percent into the SMA mixture; to identify voids in mixture (VIM) in the refusal density; and to identify asphalt durability as influenced by water by using immersion test. In this research, testing was conducted in stages, which comprised testing of the coarse and fine aggregates, filler, asphalt; and testing of mixture, which comprised standard Marshall testing, refusal density and immersion testing. The tests were based on SNI, which is the specification refered to by Bina Marga Year 2010 (second revision), and also Bina Marga specification Year 1993 (Split Mastic Asphalt). Addition of Roadcell-50 to the Split Mastic Asphalt mixture can improve Marshall Parameter index such as index stability, residual stability, flow and water void percentage. The results showed that the highest stability index was 920 kg, which was found for 0.2 percent of Roadcell-50. The highest flow index was 3.9 mm, which was found for 0.3 percent of Roadcell-50. The highest water void was 4.6 percent, which was found for 0.3 percent of Roadcell-50. The highest immersion index is was 97.35 percent, which was found for 0.2 percent of Roadcell-50. The highest VIM refusal density was 3.8 percent, which was found for 0.3 percent of Roadcell-50. Optimum Roadcell-50 content percentage that can be used as reference in planning Split Mastic Asphalt mixture is 0.2 percent, since it gives the highest stability which is 920 kg, and the highest immersion index or residual stability, which is 97.35 percent.